2012
DOI: 10.1016/j.nedt.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of student midwives' experiences of the Objective Structured Clinical Examination assessment process

Abstract: Abstract:This paper reports on a qualitative descriptive study that explored student midwives experiences of the Objective Structured Clinical Examination assessment process for obstetric emergencies within a university setting. The development of fundamental clinical skills is an important component in preparing students to meet the responsibilities of a midwife. There is an international concern that the transfer of midwifery education into universities may impact on the development of midwifery clinical ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 29 publications
8
50
0
2
Order By: Relevance
“…It provides a level of objectivity in how competency is assessed [32]. The review identified a number of benefits from using OSCE including the achievement of deeper meaningful learning [19], deeper consequential learning [20], and an increase in students' confidence in practice [33]. The OSCE was also identified as a means to facilitate the assessment of psychomotor skills, as well as knowledge and attitudes [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a level of objectivity in how competency is assessed [32]. The review identified a number of benefits from using OSCE including the achievement of deeper meaningful learning [19], deeper consequential learning [20], and an increase in students' confidence in practice [33]. The OSCE was also identified as a means to facilitate the assessment of psychomotor skills, as well as knowledge and attitudes [20].…”
Section: Discussionmentioning
confidence: 99%
“…These include the objective structured clinical examinations (OSCEs) [1] that have numerous advantages over other observation tools [17], such as the development of student's self-confidence [18], the grounding of more expressive learning [19], and the assessment of not only psychomotor skills but also allows for the assessment of knowledge and attitudes [20]. The OSCE, however, is not the only assessment tool used in nursing education.…”
Section: Introductionmentioning
confidence: 99%
“…En Irlanda, en el departamento de Ciencias de Enfermería de la Universidad de Limerick, en un estudio descriptivo cualitativo, se concluyó que la estrategia provee a los estudiantes de obstetricia una oportunidad para responder a las emergencias obstétricas en una situación simulada y contribuye a su preparación para la práctica. Además indica que la profundidad del aprendizaje brinda seguridad de que estos estudiantes serán practicantes seguros y competentes 13 .…”
Section: Introductionunclassified
“…Several authors have highlighted the importance of using OSCEs as an assessment method in health care education [1,[4][5][6]. The OSCE facilitates the assessment of student's competency with clinical skills in a controlled simulated environment instead of in the practice setting [5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of benefits have been attributed to the use of OSCEs including, the development of students confidence [7], the preparation of students for clinical practice and the achievement of deeper more meaningful learning [6]. Importantly, the use of OSCEs facilitates the assessment of psychomotor skills as well as knowledge and attitudes [5] OSCEs provide students with feedback on their clinical performance and facilitate the identification of strengths and weaknesses [4].…”
Section: Introductionmentioning
confidence: 99%